Some Evidentiary Problems in the Fight Against Money Laundering: International Legal Framework and Its Projection on the Spanish System - Hermida, Ágata María Sanz (Journal of Leadership, Accountability and Ethics, 2021)
The fight against money laundering represents significant difficulties for the States, among which are the difficulties related to the proof of this crime. The complexity of its typical configuration, its link to a previous criminal activity and the need to prove the intentional elements characterizing these offenses makes it necessary to resort to the use of circumstantial evidence. This form of proving money laundering is generally accepted in international treaties and conventions in this area. This article shall analyze the evidentiary standards used by the Spanish Supreme Court to convict for money laundering.